Persepsi Guru tentang kepemimpinan Kepala Sekolah di SD Negeri dan SD Swasta di wilayah Bogor - Prisilla Aulia Aulia; Santy Kurniasih; Neng Tyas Ananda Putri; Rusi Rusmiati Aliyyah (Universitas Djuanda Bogor, 2026)
Principal leadership is a critical factor influencing organizational quality, work climate, and teacher performance. However, there remains a gap in understanding how leadership practices differ between state and private schools operating within distinct institutional contexts. This comparative qualitative study aims to describe and compare the core leadership practices of both school types, based on survey data collected from 26 teachers across six primary schools in the Bogor area. Thematic analysis using ATLAS.ti was conducted to explore the patterns of leadership behavior. The results demonstrated that the institutional context significantly determines leadership stability. State school principals display high consistency in providing formal support, consensus-based communication, and maintaining stable work structures. Conversely, private school principals face limitations on autonomy due to foundation intervention, resulting in behavioral inconsistency, uneven professional support, and the risk of destructive leadership caused by poor emotional management. This research concludes that the failure of emotional control and structural limitations are key factors damaging the work climate in private schools. This finding emphasizes the need for context-sensitive leadership development, either through strengthening bureaucratic systems in state schools or increasing autonomy and role stability in private schools.